Effectiveness of Multidisciplinary Group-Based Intervention versus Individual Physiotherapy for Improving Chronic Low Back Pain in Nursing Staff: A Clinical Trial with 3- and 6-Month Follow-Up Visits from Tehran, Iran - Leila Ghadyani (Asian Spine Journal, 2017)
Study DesignClinical trial.PurposeTo evaluate the effectiveness of a multidisciplinary group-based intervention on improving pain and disability among Iranian nurses with chronic low back pain in Tehran, Iran.Overview of LiteratureAlthough low back pain (LBP) is one of the most important health problems, the challenge remains on how to find an effective intervention to reduce pain and related disabilities.MethodsOverall, 136 eligible nurses with chronic mechanical LBP were classified into two groups. The intervention group (n=66 participants) participated in a physiotherapy educational program (for 120 minutes) plus a health educational program based on predictive constructs of the social cognitive theory (for 120 minutes). These interventions were delivered by a physiotherapist and a health education specialist. The control group (n=70 participants) participated in a physiotherapy educational program (for 120 minutes). Disability rate, pain severity, and back pain prevention behavior were measured initially and at 3- and 6-month follow-up visits using the visual analogue scale, Roland-Morris Disability, and Nursing Low Back Pain Preventive Behaviors Questionnaire. Data were analyzed by SPSS ver. 16.ResultsThere were statistically significant differences between the two groups in the main outcome measures immediately after the educational program and at 3- and 6-month follow-up visits. Preventive behaviors of participants in the intervention group were improved at 3- and 6- month follow-up visits (p<0.001). The mean scores of predictive constructs regarding LBP preventive behaviors in the intervention group were improved after 3 and 6 months (p<0.001). Finally, in the intervention group, pain severity and disability were decreased significantly.ConclusionsThis study showed that a multidisciplinary educational program intervention can be an effective approach for reducing LBP and related disabilities among nurses.